Extravascular Dermal Trypanosomes in Suspected and Confirmed Cases of gambiense Human African Trypanosomiasis. (8th July 2020) - Camara, Mariame; Soumah, Alseny M'mah; Ilboudo, Hamidou; Travaillé, Christelle; Clucas, Caroline; Cooper, Anneli; Kuispond Swar, Nono-Raymond; Camara, Oumou; Sadissou, Ibrahim; Calvo Alvarez, Estefania; Crouzols, Aline; Bart, Jean-Mathieu; et al.
Abstract: Background: The diagnosis of gambiense human African trypanosomiasis (gHAT) typically involves 2 steps: a serological screen, followed by the detection of living trypanosome parasites in the blood or lymph node aspirate. Live parasites can, however, remain undetected in some seropositive individuals, who, we hypothesize, are infected with Trypanosoma brucei gambiense parasites in their extravascular dermis. Methods: To test this hypothesis, we conducted a prospective observational cohort study in the gHAT focus of Forecariah, Republic of Guinea. Of the 5417 subjects serologically screened for gHAT, 66 were enrolled into our study and underwent a dermatological examination. At enrollment, 11 seronegative, 8 unconfirmed seropositive, and 18 confirmed seropositive individuals had blood samples and skin biopsies taken and examined for trypanosomes by molecular and immunohistological methods. Results: In seropositive individuals, dermatological symptoms were significantly more frequent, relative to seronegative controls. T.b. gambiense parasites were present in the blood of all confirmed cases (n = 18) but not in unconfirmed seropositive individuals (n = 8). However, T. brucei parasites were detected in the extravascular dermis of all unconfirmed seropositive individuals and all confirmed cases. Skin biopsies of all treated cases and most seropositive untreated individuals progressively became negative for trypanosomes 6 and 20 months later. Conclusions: Our results highlight the skin as a potential reservoir for African trypanosomes, with implications for our understanding of this disease's epidemiology in the context of its planned elimination and underlining the skin as a novel target for gHAT diagnostics. Abstract : Live trypanosomes can remain undetected in the blood of individuals seropositive for sleeping sickness. Here, we show that they could be infected with parasites in their extravascular dermis, highlighting the skin as a potential reservoir for trypanosomes.